Karakteristik Naskah Kamus Semantik Bahasa Arab Karya Syekh Abdul Latif Syakur - Ridhoul Wahidi (Masyarakat Pernaskahan Nusantara, 2024)
This article aims to describe the characteristics of the manuscript of the Arabic Semantic Dictionary by Sheikh Abdul Latif Syakur from the philological and historicity aspects of the author. The important points that will be discussed in this article are aspects of manuscripts and texts, systematics of manuscript preparation, manuscript reference sources, use of Arabic and Malay Arabic script, lexical meaning, use of Arabic grammar and development of meaning. The entire picture can be obtained by using qualitative methods that are library research. The approach used in this article is philological and historical. Aspects of philology as describing manuscripts, translation and criticism of texts. Historical aspect to reveal the author's background which presents the author's intellectual elements. From there you can get a complete picture of the characteristics of an ancient manuscript, namely the Arabic Semantic Dictionary written by Sheikh Abdul Latif Syakur. === Artikel ini bertujuan untuk mendeskripsikan karakteristik naskah Kamus Semantik Bahasa Arab Karya Syekh Abdul Latif Syakur dari aspek filologi dan historisitas pengarangya. Poin-poin penting yang akan dibahas dalam artikel ini adalah aspek naskah dan teks, sistematika penyusunan naskah, intertekstual naskah, penggunaan aksara Arab dan Arab melayu, makna leksikal, penggunaan gramatika Arab dan pengembangan makna. Seluruh gambaran tersebut diperoleh dengan menggunaka metode kualitatif bersifat library research. Pendekatan yang digunakan dalam artikel ini adalah filologi dan linguistik. Aspek filologi untuk mendeskripsikan manuskrip, alih bahasa dan kritik atas teks. Aspek linguistik mengungkap aspek kebahasaan manuskrip ini. Dari sanalah dapat diperoleh gambaran utuh mengenai karakteristik sebuah naskah kuno, yakni naskah Kamus Semantik Bahasa Arab yang ditulis oleh Syekh Abdul Latif Syakur.